IMPLEMENTATION OF MINISTRY OF AGRICULTURE REGULATION NO. 49 OF 2020 ON SUBSIDIZED FERTILIZERS IN TONRORITA VILLAGE, BIRINGBULU DISTRICT, GOWA REGENCY: A SIYASAH SYAR’IYYAH PERSPECTIVE - Harifin,; B, Halimah; Hisbullah, (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This study aims to determine how the implementation of the Ministry of Agriculture in the management of subsidized fertilizers and the perspective of Siysah Syar'iyyah in the distribution of fertilizers in the village of Tonrorita, sub-district. Biringbulu Kab. Gowa, based on the Decree of the Minister of Agriculture Regulation No. 49 of 2020 concerning the Allocation and Highest Retail Price of Subsidized Fertilizer. The method used in this research is descriptive qualitative and data acquisition is done through structured interviews, field observations and documentation. The results showed that fertilizer management in Tonrorita sub-district went through several stages, namely socialization, preparation of the RDKK (Definitive Plan for Group Needs), distribution/distribution and reporting, but in its application it was still not optimal. This is because of the abuse of authority carried out by GAPOKTAN (Association of Heads of Farmers Groups), and Head of farmer groups in distributing fertilizers to farmers and the application of prices that are not in accordance with the HET (Highest Retail Price) of subsidized fertilizers, which results in a lack of fertilizer supply. which must be spread to farmers because of manipulation by Gapoktan